2002
DOI: 10.1016/s0092-8674(02)01136-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Internalin, a Major Invasion Protein of Listeria monocytogenes, in Complex with Its Human Receptor E-Cadherin

Abstract: Listeria monocytogenes, a food-borne bacterial pathogen, enters mammalian cells by inducing its own phagocytosis. The listerial protein internalin (InlA) mediates bacterial adhesion and invasion of epithelial cells in the human intestine through specific interaction with its host cell receptor E-cadherin. We present the crystal structures of the functional domain of InlA alone and in a complex with the extracellular, N-terminal domain of human E-cadherin (hEC1). The leucine rich repeat (LRR) domain of InlA sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
275
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 262 publications
(283 citation statements)
references
References 52 publications
7
275
0
1
Order By: Relevance
“…Recently, a new PAl specific for L. ivanovii, called LIPI-2, containing eight new inl genes and a further gene encoding a protein of unknown function, has been described (21). As already reported for L. monocytogenes, InlA and In18, the intemalins carried by LIPI-2, have been shown to be responsible for the specific pathogenic properties of L. ivanovii, mediating the recognition of host-, tissue-or cell-specific receptors (32)(33)19). The specific interaction of InlA with its receptor E-cadherin is fundamental in the tropism of L. monocytogenes for human epithelial cells (34), and it has been suggested that the variety of internal ins in the different Listeria spp.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, a new PAl specific for L. ivanovii, called LIPI-2, containing eight new inl genes and a further gene encoding a protein of unknown function, has been described (21). As already reported for L. monocytogenes, InlA and In18, the intemalins carried by LIPI-2, have been shown to be responsible for the specific pathogenic properties of L. ivanovii, mediating the recognition of host-, tissue-or cell-specific receptors (32)(33)19). The specific interaction of InlA with its receptor E-cadherin is fundamental in the tropism of L. monocytogenes for human epithelial cells (34), and it has been suggested that the variety of internal ins in the different Listeria spp.…”
Section: Discussionmentioning
confidence: 87%
“…This earlier report showed that point mutations which prevent Ca 2+ binding in the junction between EC1 and EC2, and ablate Ca 2+ -dependent dimerization, adversely affect § E g 7 binding, implying that dimerization is required. Crystallographic structures and chemical shift data of Ecadherin EC1 show that the point mutations or the loss of Ca 2+ in the domain junction would have little or no affect on the integrin binding site [29,39]. However, with loss of interdomain Ca 2+ , the domain junction loses rigidity and permits a wide angle of free movement of EC1, relative to the rest of the molecule [29].…”
Section: Discussionmentioning
confidence: 99%
“…65 The crystal structure of the LRR region of InlA in association with the extracellular domain of human E-cadherin corroborated this observation and revealed that a hydrophobic pocket on the LRR accommodates the E-cadherin proline 16 residue. 66 Oral inoculation of a transgenic mouse model that synthesizes the human E-cadherin in the intestine showed the crucial role of InlA in the crossing of the intestinal epithelium. 67 The role of this interaction in the process of placental infection is still not clear and different studies have provided contradicting results.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%